Analysis of Environmentally Friendly Product Selection by Millennials and Gen Z in the Indonesian Market - Sudirjo, Frans; Padila, Dila; Auliya, Salwa (Westscience Press, 2024)
This research delves into the analysis of factors shaping the selection of environmentally friendly products by Millennials and Generation Z in the Indonesian market. Through a quantitative approach, data was collected via surveys to understand the influence of variables such as price sensitivity, brand reputation, convenience, product quality, and perceived environmental impact on product selection. The findings reveal significant insights into consumer preferences and behaviors, shedding light on the importance of sustainability considerations in driving purchasing decisions among younger demographics. The implications of this research extend to businesses aiming to align with eco-conscious trends and policymakers seeking to promote sustainable consumption patterns in Indonesia.